Mesa redonda: ¿Constitucionalización del Derecho Civil o civilización del Derecho Constitucional? - Landa Arroyo, César Rodrigo (2024)
In this round table, six questions are addressed regarding the novel discussion on the possible constitutionalization of Civil Law or, on the contrary, the civilization of Constitutional Law. From different doctrinal perspectives, experts in both topics analyze the existence and characteristics of this latent legal phenomenon. It is emphasized, on the one hand, that the modernization of the Rule of Law has strengthened the protection of human rights, irradiating constitutional values to civil legislation. But also, it is the constitutional courts that play a crucial role in ensuring civil rights through principles of reasonableness and proportionality.On the other hand, it is argued that civil law must be interpreted in the light of the Constitution, as the fundamental law that expresses the values of the legal system. However, it is noted that constitutional interpretation is not always automatic or objective, and may vary according to the method used, which introduces a degree of subjectivity and risk of ideologically motivated decisions.From this valuable confrontation of ideas, the reader can reach his own conclusions, since the debate is broad, rich and undefined.